Overview of the Risk of Postpartum Depression in Mothersfollowing a Caesarean Section in a General Hospital Bali Mandara Region Bali Province - Komang Widya Puspita; Ni Wayan Suarniti; Ni Made Dwi Mahayati (Jurnal EduHealth, 2026)
This study was motivated by the higher risk of postpartum depression in mothers undergoing cesarean section (CS) compared to vaginal delivery. Physical trauma, prolonged recovery, and feelings of failure are key factors. Data shows that postpartum depression affects 46.7% of post-CS mothers, much higher than 2.2% in vaginal deliveries. This research aims to analyze postpartum depression risk among post-CS mothers at Bali Mandara Hospital by examining factors such as age, education, pregnancy status, marital status, parity, economic status, and spousal support. A descriptive quantitative method was employed, with a sample of 43 post-CS mothers collected from March to April 2025. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) and analyzed univariately. The results showed most respondents were over 35 years old (44.1%), highly educated (58.1%), and had strong spousal support (79%). The majority (74.4%) exhibited low depression risk, while 14% had moderate risk. Planned pregnancy, marital status, multiparity, income above minimum wage, and strong spousal support reduced depression risk. In conclusion, postpartum depression risk among post-CS mothers at Bali Mandara Hospital is low due to adequate protective factors. Healthcare providers should conduct routine screening, provide psychosocial interventions for high-risk mothers, and enhance family education on postnatal support.